Persepsi Mahasiswa Penerima Kip Kuliah Terhadap Literasi Keuangan dan Pengaruhnya Pada Kesejahteraan Finansial di Institut Bisnis Dan Teknologi Kalimantan - Normalina Normalina; Ari Irawan (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the perception of Kartu Indonesia Pintar (KIP) Kuliah scholarship recipients on financial literacy and its impact on their financial well-being. A descriptive qualitative approach was applied through in-depth interviews with students at the Institut Bisnis dan Teknologi Kalimantan. The findings indicate that financial literacy plays a vital role in students' personal financial management. Students with higher financial literacy levels tend to manage their educational aid more wisely and demonstrate stronger financial planning skills. The study also identifies key challenges, such as the lack of formal financial education and the influence of a consumptive lifestyle. These findings highlight the importance of integrating financial literacy into higher education to enhance students’ financial well-being